A subepithelial lesion algorithm for endoscopic (SAFE) resection in the upper gastrointestinal tract - Gupta, Sunil; Gauci, Julia; O'Sullivan, Timothy; Cronin, Oliver; Whitfield, Anthony; Craciun, Ana; Awadie, Halim; Yang, Jing; Kwan, Vu; Lee, Eric Y. T.; Burgess, Nicholas G.; Bourke, Michael J. (Endoscopy, 2024)
Background Complete excision of upper gastrointestinal subepithelial lesions (U-SELs) eliminates diagnostic uncertainty, obviates the need for surveillance, and may be necessary for definitive diagnosis and management. Current guidelines lack precision and cohesion, and surgery is associated with significant morbidity. We describe and report on the outcomes of our SEL algorithm for endoscopic (SAFE) resection.Methods U-SELs were enrolled prospectively over 115 months until March 2023. All subjects underwent axial (computed tomography) imaging and endoscopic ultrasonography (EUS) to exclude a large exophytic component or invasion into local structures, and assess for muscularis propria (MP) involvement.Results 106 U-SELs (41 esophageal, 65 gastric) were resected (mean patient age 60.6 [SD 13.4]; 51.9% male). Esophageal U-SELs underwent endoscopic submucosal dissection (ESD; n = 22) or submucosal tunneling endoscopic resection (STER) if MP involvement was suspected (n = 19). Gastric U-SELs underwent STER (n = 6 at cardia), ESD (n = 47), or exposing endoscopic full-thickness resection (e-EFTR; n = 12). Technical success rates were 97.6% and 92.3%, respectively. Among the noncardiac gastric U-SELs, five resections (9.6%) were completed laparoscopically owing to deep and broad full-thickness involvement; five (9.6%) required laparoscopic gastrotomy and surgical retrieval after successful resection and closure owing to a large lesion size (mean 47 mm). There was no delayed bleeding, perforation, or recurrence at 13 months.Conclusion U-SELs may be effectively and safely treated by endoscopic resection. The SAFE approach provides a framework that facilitates structured decision-making. Esophageal U-SELs suspected of involving the MP should undergo STER. Gastric SELs are best managed by ESD, with a view to proceeding to e-EFTR. A laparoscopic upper gastrointestinal surgeon should be available in case surgical retrieval of the specimen or laparoscopic completion is required.